Readiness factors for lean implementation in healthcare settings – a literature review. Issue 2 (13th May 2014) - Al-Balushi, S.; Sohal, A.S.; Singh, P.J.; Al Hajri, A.; Al Farsi, Y.M.; Al Abri, R.
Abstract : Purpose: – The purpose of this paper is to determine the readiness factors that are critical to the application and success of lean operating principles in healthcare organizations through a review of relevant literature. Design/methodology/approach: – A comprehensive review of literature focussing on lean and lean healthcare was conducted. Findings: – Leadership, organizational culture, communication, training, measurement, and reward systems are all commonly attributed readiness factors throughout general change management and lean literature. However, directly related to the successful implementation of lean in healthcare is that a setting is able to authorize a decentralized management style and undertake an end-to-end process view. These can be particularly difficult initiatives for complex organizations such as healthcare settings. Research limitations/implications: – The readiness factors identified are based on a review of the published literature. The external validity of the findings could be enhanced if tested using an empirical study. Practical implications: – The readiness factors identified will enable healthcare practitioners to be better prepared as they begin their lean journeys. Sustainability of the lean initiative will be at stake if these readiness factors are not addressed. Originality/value: – To the best of the knowledge, this is the first paper that provides a consolidated list of key lean readiness factors that can guide practice, as well as future theory and empirical research.